Effect of Tamsulosin on Stone Clearance after Extra-corporeal Shock Wave Lithotripsy (Bangladesh Medical Journal, 2012)
This prospective study was performed to observe effect of Tamsulosin on stone clearance after Extra-corporeal Shock Wave Lithotripsy (ESWL) for renal stones having size 6-20 mm. According to selection criterion total 80 patients with renal stones were divided into two groups. In group l, 40 patients treated with traditional hydrotherapy after ESWL and in group 2 another 40 patients were treated with additional Tamsulosin. In-group 1, there were 25 male and 15 female patients and in group 2, male and female patients were 30 and 10 respectively. Without considering the stone size within 3 weeks after ESWL stone clearance in group 1 and 2 was 57.50 and 80.00 percent respectively (P0.05). In cases of smaller stones, clearance was 100% and 77.8% among group 1 and 2 respectively without any significant difference (P>0.05). But in larger stones, stone clearance was 34.60% and 81.8% among group 1 and 2 respectively and there was a statistically significant difference in clearance between the groups (P